2012
DOI: 10.9790/0853-0212733
|View full text |Cite
|
Sign up to set email alerts
|

Surface Contamination in Skin and Room during Hospitalization of Thyroid Cancer Patient Receiving Radioiodine Ablation

Abstract: The large amount of iodine-131 (131 I) activity excreted by the patient via perspiration, saliva, breath and urine during hospitalization may develop radiation contamination hazard. The aim of this study was to measure the level of contamination activity from skin and room surfaces throughout radioiodine ablation patient's hospitalization and to determine the correlation between the administrated dose and level of contamination activity from skin and room surfaces. The removable activity was measured from nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Depending upon the renal clearance rates and other patient specific factors, the contamination level varies from patient to patient. The excretory channels for administered radionuclide in therapy are micturition, bowel, salivation, sweating, lachrymal fluid and lactation [28]. Other factors affecting the clearance levels in thyroid carcinoma patients are the variable amount of thyroid remnants, renal insufficiency and patients behaviour like following proper hygiene such as cleaning urine contamination in toilet, faulty urination style causing spillage of urine on flour, clothes changing frequency, bathing frequency, and water intake routine [14].…”
Section: Resultsmentioning
confidence: 99%
“…Depending upon the renal clearance rates and other patient specific factors, the contamination level varies from patient to patient. The excretory channels for administered radionuclide in therapy are micturition, bowel, salivation, sweating, lachrymal fluid and lactation [28]. Other factors affecting the clearance levels in thyroid carcinoma patients are the variable amount of thyroid remnants, renal insufficiency and patients behaviour like following proper hygiene such as cleaning urine contamination in toilet, faulty urination style causing spillage of urine on flour, clothes changing frequency, bathing frequency, and water intake routine [14].…”
Section: Resultsmentioning
confidence: 99%
“…Even though some guidelines recommend drinking ample water to assist in the elimination of radioactivity on the basis of enhanced diuresis, there is however no large body of evidencebased literature to support this [16][17][18]. In fact, Haghighatafshar et al [18] showed that although inadequate fluid intake and dehydration may reduce the excretion of iodine, increas- ing fluid intake and urinary flow above the physiological range does not significantly increase excretion of RAI.…”
Section: Discussionmentioning
confidence: 99%
“…Radioiodine (I-131) is primarily β-emitting radionuclide with 610 keV energy followed by a 364 keV photon. [1][2][3][4][5] β ray emitted from radioiodine contributes the major radiation dose to the thyroid tissue and the gamma ray photon may give rise the potential radiation hazard to others. 1,2 After first usage of I-131 by Saul Hertz and Arthur Roberts in January 1941 6 , it becomes an admired treatment option for patients with thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] β ray emitted from radioiodine contributes the major radiation dose to the thyroid tissue and the gamma ray photon may give rise the potential radiation hazard to others. 1,2 After first usage of I-131 by Saul Hertz and Arthur Roberts in January 1941 6 , it becomes an admired treatment option for patients with thyroid cancer. Obliviously the Patients administered I-131 therapeutic dosages are sources of undesir-able high radiation exposure to close family members and the general public.…”
Section: Introductionmentioning
confidence: 99%